Voluntary Feed Intakes, Feed Preferences and Growth Performance of Growing and Fattening Rabbits Under Tropical Coastal Climate of Benin. - DAHOUDA, MOHAMADOU; DOSSA, ROMAIN A. MARC; Amoussa, S.; Vidjannagni, Delphin Sévérin; ABOU, M.; YOUSSAO, ALASSANE (My University, 2019)
Good knowledge of tropical animal species requirements is required to improve their productivity. The paper describes voluntary dry matter intakes in growing and fattening rabbits as affected by tropical climate. This study aims at determining the levels of concentrate feed consumed alone or in association with fodder. Thus, two commercial concentrate feed (pellet and mash) and two fodder (Elaeis guineensis or Panicum maximum) currently used in Benin were tested. A total of 192 young rabbits were used (96 young rabbits, 35 ± 2 days old at the growth stage and 96 young rabbits, 70 ± 2 days old at the fattening stage). The amounts of single feed intake and of the association feed concentrate-fodder were recorded daily on dry matter basis. The daily quantity of feed ingested by growing rabbit was 106g of pellet alone; 81.3g of pellet + 6.7g Panicum maximum; 84.6g of pellet + 8.1g of Elaeis guineensis; 63.6g of mash alone; 42.5g of mash + 7.4g of Panicum maximum; 41.1g of mash + 12.9g of Elaeis guineensis. The fattening rabbits ingested 129.9g of single pellet; 112.8g of pellet + 15.2g of Panicum maximum; 98.6g of pellet + 14.3g of Elaeis guineensis; 78.6g of single mash; 72.9g of mash + 20.1g of Panicum maximum; 66.7g of mash + 26.0g of Elaeis guineensis. The pellet diet was better appreciated and the better growth and Daily Weight Gain (DWG) was obtained with the pellet diets than mash and the addition of fodder mostly improved the ingestion of the mash diet in fattening rabbits.
Keywords: Benin; Feed Preferences; Rabbits; Voluntary Feed Intake